2015
DOI: 10.1016/j.ebiom.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Telomere G-tail Length is a Promising Biomarker Related to White Matter Lesions and Endothelial Dysfunction in Patients With Cardiovascular Risk: A Cross-sectional Study

Abstract: BackgroundThe telomeric 3′-overhang (G-tail) length is essential for the biological effects of telomere dysfunction in vitro, but the association of length with aging and cardiovascular risk is unclear in humans. We investigated the association between the telomere G-tail length of leukocytes and cardiovascular risk, age-related white matter changes (ARWMCs), and endothelial function.MethodsPatients with a history of cerebrovascular disease and comorbidity were enrolled (n = 102; 69 males and 33 females, 70.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Additional protein-protein interactions mediate the communication of telomeres with structural components of the cell nucleus (16). Because of its crucial role in chromosome protection, it has been recently suggested that shorter G-tail length is more directly associated with age and higher disease risk factors than total telomere length (TL) (17), suggesting G-tail as a new potential biomarker, alternative to TL per se (18). Besides shelterin, G-quadruplexes are other higher-order structures, protecting the 3' overhang of telomeres from being accessed by the enzyme telomerase (19).…”
Section: Telomere-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional protein-protein interactions mediate the communication of telomeres with structural components of the cell nucleus (16). Because of its crucial role in chromosome protection, it has been recently suggested that shorter G-tail length is more directly associated with age and higher disease risk factors than total telomere length (TL) (17), suggesting G-tail as a new potential biomarker, alternative to TL per se (18). Besides shelterin, G-quadruplexes are other higher-order structures, protecting the 3' overhang of telomeres from being accessed by the enzyme telomerase (19).…”
Section: Telomere-binding Proteinsmentioning
confidence: 99%
“…A lot of effort has been done to evaluate whether clinical practice could benefit from TL measurement; © 1996-2018 Recent discoveries showed that DNA can be damaged also with normal TL, if G-tail structure is disrupted, suggesting, that G-tail length contributes more to pathologies than TL itself (18). It has been associated with age and vascular risk factors (17) and methods for the examination of G-tail length with a high-throughput platform using genomic DNA or cell lysate are faster than classical methods for TL determination, giving G-tail priority as a biomarker choice in the future studies (127).…”
Section: Telomeres As a Biomarkermentioning
confidence: 99%
“…According to the general theory, telomere length is inversely correlated with age. In addition, it has been reported that the telomeric 3’-overhang (G-tail) length is associated with a risk of cardiovascular events [5, 6]. However, the significance of telomere/G-tail length in LT has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…According to their observations, G-tail length decreases with age ( Nezu et al, 2015 ). This would be in agreement with previous observations that telomere shortening is accompanied by G-tail shortening.…”
mentioning
confidence: 99%
“…But until recently, whether or not this is the case in the clinical settings has remained elusive. In this issue of EBioMedicine , using a highly sensitive and quantitative method, Nezu, Tahara and colleagues quantitated both G-tail and total telomere length of leukocytes in patients with a history of cerebrovascular disease or atypical neurological problems ( Nezu et al, 2015 ). Cross-sectional analyses revealed that G-tail length, rather than total telomere length, is associated with endothelial function and severity of age-related white matter changes.…”
mentioning
confidence: 99%